The comparative analysis of English and Lithuanian transport terms and some methods of developing effective science writing strategies by non‐native speakers of English - Marina, Valerija; Marin, Igor; Snuviškienė, Genovaitė (Transport, 2009)
The paper addresses the problem of developing more effective strategies and skills of writing scientific and technical texts by non‐native speakers of English. The causes of poor writing are identified and general guidelines for developing effective science writing strategies are outlined. The analysis of difficulties faced by non‐native speakers of English in writing research papers is made by examining transport terms and international words which are based on different nomination principles in English and Lithuanian. Case study of various names given to a small vehicle used for passenger transportation in many countries is provided, illustrating the alternative ways of naming the same object of reality in different languages. The analysis is based on the theory of linguistic relativity. Differences in the use of similar international terms in English and Lithuanian, which often cause errors and misunderstanding, are also demonstrated. The recommendations helping non‐native speakers of English to avoid errors and improve skills of writing scientific and technical texts are given.First published online: 27 Oct 2010